Genetic diversity of walnut (Juglans regia L.) seedlings through SSR markers in north-western Himalayan region of Jammu (Bangladesh Journal of Botany, 2020)
screening of 25 SSR markers, revealed 23 clear and consistent amplification profiles in the entire walnut germplasm set. A total of 54 alleles were amplified by SSR primers and the number of alleles range from 2 to 3. The PIC value ranged from 0.36 to 0.68. The dendrogram classified all genotypes into two main clusters with various degrees of subclustering. Estimated genetic dissimilarity coefficient ranged from 0.36 to 0.85. Through model-based cluster analysis all genotypes were grouped into 5 genetically distinct subpopulations. The expected heterozygosity at a given locus was found to range from 0.520 to 0.5477. Similarly, population differentiation measurements (Fst) ranged from 0.2286 to 0.2909. These findings would be helpful for decision making in future walnut breeding studies, germplasm management activities to maximize genetic diversity in walnut germplasm and may also prove useful in future for conducting association mapping in walnut for different traits.